1990
DOI: 10.1021/ma00220a016
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric catalysts based on 4-(diallylamino)pyridine

Abstract: Copolymers of 4-(diallylamino)pyridine (DAAP) with neutral, anionic, and cationic monomers were investigated as catalysts for esterolysis and esterification reactions. The former were carried out with p-nitrophenyl caproate as substrate in water at 30 °C and pH values ranging from 7 to 9. The copolymers proved in many cases to be more effective than the homopolymer of DAAP, which in turn was more active than the very effective low molecular weight nucleophilic catalyst 4-pyrrolidinopyridine (PPY). The specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The macromolecule 1 is an amphiphilic polymer containing distinct hydrophobic and hydrophilic regions. The catalytic center of macromolecule 1 is the 4-(dialkylamino)pyridine group and the hydrophobic association of substrate to catalyst in the reaction medium is responsible for the rate enhancements observed in the 1 -catalyzed solvolysis reaction of 2 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The macromolecule 1 is an amphiphilic polymer containing distinct hydrophobic and hydrophilic regions. The catalytic center of macromolecule 1 is the 4-(dialkylamino)pyridine group and the hydrophobic association of substrate to catalyst in the reaction medium is responsible for the rate enhancements observed in the 1 -catalyzed solvolysis reaction of 2 . …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the copolymer composition and the surrounding medium, amphiphilic macromolecules can also form aggregates with multiple morphologies . Extensive studies have shown that the increase of hydrophobic effects of amphiphilic macromolecules, i.e., the increase in ratio of hydrophobic to hydrophilic components and the addition of salting-out agents, leads to changes of aggregate morphology from spheres to rods, and to vesicles in appropriate solvents. , 4-(Dialkylamino)pyridine-functionalized polymers have been regarded as useful and simple model systems for obtaining a better understanding of the origins of enzymic efficiency and selectivity. Recently, we have reported ion-induced substrate specificity in solvolysis of p -nitrophenyl alkanoates 2 ( n = 2−18) catalyzed by polymer 1 containing the 4-(dialkylamino)pyridine functionality and a bis(trimethylene)disiloxane backbone (Scheme ) . The tris(hydroxymethyl)methylammonium ion as a salting-in ion induces the same substrate specificity for 2 ( n = 6) in aqueous Tris buffer solution that is obtained with cholesterol esterase for the same hydrolysis reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Macromolecule 1 is an amphiphilic polymer which contains distinct hydrophobic and hydrophilic regions, and it associates to form macromolecular aggregates by self-assembly in aqueous or methanol−water solution. The control of aggregate morphology changes of small-molecule and macromolecular amphiphiles from spheres to rods, and to vesicles by increasing the hydrophobic effects in water and water−organic solvent mixtures has already been well-established. For many years, the aggregate morphology changes of small-molecule amphiphiles from spherical micelles to micellar rods and vesicles have been known to be controlled by increases of their constituent concentrations in solution. The gradual changes of aggregate morphology of polystyrene- b -poly(2-vinylpyridine) copolymers from spheres to rods, and to vesicles have also been demonstrated with increasing copolymer concentration . Consistent with the notion that salt-induced hydrophobic effects control aggregate morphology of amphiphiles, the aggregate morphology of these copolymers in water−organic solvent mixtures can also be changed from spheres to rods, and to vesicles by addition of salting-out agents such as NaCl and CaCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…4-(Dialkylamino)pyridine-functionalized polymers have been regarded as useful and simple model systems for obtaining a better understanding of the origins of enzymic efficiency and selectivity. We have recently made an attempt to investigate such a model system to gain insight into the dominant control factors in solvolysis of p -nitrophenyl esters 2 ( n = 2−18) catalyzed by 4-(dialkylamino)pyridine-functionalized polymer 1 . The mechanism of the reaction involves the attack by nucleophile 1 at the carbonyl group of substrates 2 and the formation of an N -acylpyridinium intermediate where the breakdown of the intermediate is the rate-determining step in the catalytic reactions . Strikingly, we have found ion-induced substrate specificity in the 1 -catalyzed solvolysis of 2 ( n = 2−18) in aqueous and methanol−water solutions. , Salting-in effects of the tris(hydroxymethyl)methylammonium ion in aqueous Tris buffer solution lead to the same substrate specificity for 2 ( n = 6) that is obtained with the enzyme, cholesterol esterase, for the same hydrolysis reaction …”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the p K a of polyvinylamine (PVAm) is ∼10 . Pyr groups are among the most potent alkylaminopyridine nucleophiles known that can be present in vinylic polymers. Hence, a copolymer of Pyr that also contains primary amino groups would maintain nucleophilicity and yet be capable of facile covalent attachment to functional surfaces. Furthermore, we hypothesized that formation of the urea bonds between the amino groups of our polymers and properly chosen aliphatic isocyanates would provide sufficient hydrophobicity to the resulting composite, which would promote interaction with the amphiphilic organophosphate electrophiles.…”
Section: Introductionmentioning
confidence: 99%